Biomass polyester adhesive, preparation method thereof, diaphragm, battery and electric device

By using biomass polyester adhesives in lithium battery separators, the problems of weakening the bonding interface of traditional adhesives at high temperatures and degradation of the diaphragm wetting performance are solved, and the high wetting performance and thermal stability of the coating film are achieved, which improves the Battery application reliability and applicability.

CN119119938APending Publication Date: 2024-12-13SHANGHAI ENERGY NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411269494.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The use of traditional adhesives in lithium battery separators has the problem of weakening the bonding interface under high temperature conditions and degradation of the separator wetting performance, which affects the stability and performance of the battery.

Method used

Using biomass polyester adhesive, its block units are prepared by polycondensation reaction of 2,5-furandiformate and trihydroxy melamine resin alcohol, and added to the diaphragm coating to improve the wetting performance and thermal stability of the coating film. sex.

Benefits of technology

It significantly reduces the contact angle of the coating film and the heat shrinkage rate of 1 h at 150°C, enhances the reliability and applicability of the membrane, and improves the heat resistance and wetting performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119938A_ABST
    Figure CN119119938A_ABST
Patent Text Reader

Abstract

The invention discloses a biomass polyester adhesive, a preparation method thereof, a diaphragm, a battery and an electric device, and belongs to the field of batteries. The biomass polyester adhesive has the following block units: # imgabs 0 #, R1 and R2 are respectively chain segment repeating units or H, at least one of three R1 and three R2 is a chain segment repeating unit, the chain segment repeating unit is # imgabs 1 #, and the value of n is 1-5. The biomass polyester adhesive provided by the invention has better wettability, high heat resistance and good adhesive force and durability, the biomass polyester adhesive is beneficial to improving the wettability of the surface of a film containing the biomass polyester adhesive, the thermal stability strength is higher, and the reliability and applicability of a diaphragm in practical application are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and more specifically, to a biomass polyester adhesive and a preparation method thereof, as well as a diaphragm, a battery, and an electrical device. Background Art

[0002] As a new type of power source with high performance and high energy density, lithium batteries have important applications in electric vehicles, wearable devices, energy storage systems and other fields. As an important component of lithium-ion batteries, the diaphragm has important functions such as isolating positive and negative electrodes, conducting ions and preventing short circuits. The application prospects of adhesives in lithium battery diaphragms are very broad, but there are some problems with the use of traditional adhesives in diaphragms. For example, under high temperature conditions, the bonding interface may become weak, thereby affecting the stability of the battery; or the diaphragm's wettability may decrease, resulting in a decrease in battery performance.

[0003] Therefore, it is very important to study an adhesive for battery separators with high heat resistance and good wetting properties. Summary of the invention

[0004] The present application provides a biomass polyester adhesive and a preparation method thereof, as well as a diaphragm, a battery, and an electrical device. The biomass polyester adhesive has excellent wetting performance, high heat resistance, good adhesion, and durability. When the above-mentioned biomass polyester adhesive is applied to the coating of the diaphragm, the wetting performance and thermal stability strength of the diaphragm surface can be improved, thereby enhancing the reliability and applicability of the diaphragm in practical applications.

[0005] The embodiment of the present application is implemented as follows:

[0006] In the first aspect, the present application provides a biomass polyester adhesive having a block unit as shown below: wherein R1 and R2 are respectively segment repeating units or H, and at least one of the three R1s and the three R2s is a segment repeating unit,

[0007] Among them, the segment repeating unit is:

[0008] The value of n is 1-5.

[0009] The biomass polyester adhesive provided in the present application has excellent wetting performance, high heat resistance, good adhesion and durability. When the above-mentioned biomass polyester adhesive is applied to the coating of the diaphragm, it is beneficial to significantly reduce the contact angle of the coating and reduce the thermal shrinkage rate at 150°C for 1h, thereby improving the wetting performance and thermal stability strength of the coating surface, and enhancing the reliability and applicability of the diaphragm in practical applications.

[0010] In some optional embodiments, the value of n is 2-4.

[0011] In a second aspect, the present application provides a method for preparing a biomass polyester adhesive, which comprises:

[0012] Dissolving 2,5-furandicarboxylic acid ester and trihydroxymelamine resin alcohol in a first organic solvent to obtain a mixed solution, adding a first catalyst to the mixed solution and performing a polycondensation reaction under anaerobic conditions to obtain a biomass polyester adhesive;

[0013] The structural formula of 2,5-furandicarboxylic acid ester is as follows:

[0014] The value of n is 1-5;

[0015] The structural formula of trihydroxymelamine resin alcohol is as follows:

[0016]

[0017] The first catalyst includes a polyoxometalate.

[0018] In the preparation method provided in the present application, the biodegradable polyester adhesive obtained by condensation reaction using specific raw materials has better wetting performance, high heat resistance, good adhesion and durability. When the above-mentioned biomass polyester adhesive is applied to the coating of the diaphragm, it is beneficial to significantly reduce the contact angle of the coating and reduce the thermal shrinkage rate at 150°C for 1h, thereby improving the wetting performance and thermal stability strength of the coating surface, thereby enhancing the reliability and applicability of the diaphragm in practical applications.

[0019] In some optional embodiments, the value of n is 2-4.

[0020] In some optional embodiments, the temperature of the polycondensation reaction is 130-150° C., and the time of the polycondensation reaction is 8-12 hours.

[0021] In some optional embodiments, the molar ratio of trihydroxymelamine resin alcohol to 2,5-furandicarboxylic acid ester is 1:1.4-1.5.

[0022] In some optional embodiments, the molar ratio of 2,5-furandicarboxylic acid ester to the first catalyst is 4-5:1.

[0023] In some optional embodiments, the first catalyst is added to the mixed solution by constant flow dripping.

[0024] In some optional embodiments, the 2,5-furandicarboxylic acid ester is prepared by the following method:

[0025] dissolving furandicarboxylic acid in a second organic solvent to obtain a furandicarboxylic acid solution;

[0026] Adding the ether alcohol and the second catalyst dropwise into the furandicarboxylic acid solution, and performing an esterification reaction under anaerobic conditions to obtain 2,5-furandicarboxylic acid esterified product;

[0027] Among them, the structural formula of ether alcohol is as follows:

[0028] The value of n is 1-5;

[0029] The second catalyst comprises a polyoxometalate;

[0030] Optionally, the value of n is 2-4.

[0031] In some optional embodiments, the molar ratio of furandicarboxylic acid to ether alcohol is 1:0.5-0.7.

[0032] In some optional embodiments, the esterification reaction temperature is 70-90° C., and the esterification reaction time is 6-8 h.

[0033] In some optional embodiments, the molar ratio of furandicarboxylic acid to the second catalyst is 20-25:1.

[0034] In some optional embodiments, the ether alcohol and the second catalyst are first mixed and then added to the furandicarboxylic acid solution by constant flow dropwise addition.

[0035] In some optional embodiments, the polyoxometallate includes silicotungstic acid and / or phosphotungstic acid.

[0036] In the third aspect, the present application provides an example of a diaphragm, which includes a base film and a coating film located on at least one surface of the base film, wherein the coating film contains the biomass polyester adhesive provided in the first aspect of the present application or the biomass polyester adhesive prepared by the preparation method provided in the second aspect of the present application.

[0037] In some optional embodiments, the mass percentage of the biomass polyester adhesive in the coating film is greater than 0 and less than or equal to 2%.

[0038] In some optional embodiments, the mass percentage of the biomass polyester adhesive in the coating film is 1%-2%.

[0039] In a fourth aspect, the present application provides a battery, which includes the separator provided in the third aspect of the present application.

[0040] In a fifth aspect, the present application example provides an electrical device, which includes the battery provided in the fourth aspect of the present application, and the battery is used to power the electrical device. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 This is the Fourier infrared spectrum of the biomass polyester adhesive prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0043] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0044] Biomass polyester adhesive

[0045] Biomass polyester adhesives have block units as shown below: Wherein R1 and R2 are respectively segment repeating units or H, and at least one of the three R1s and the three R2s is a segment repeating unit.

[0046] Among them, the segment repeating unit is: The value of n is 1-5.

[0047] The value of n is related to the chain length of the alcohol ether. The longer the chain length of the chain structure, the higher the viscosity of the polymer material, and the heat resistance, strength and toughness of the material will also be improved. However, too long a length will reduce the compactness of the network structure. Therefore, controlling the value of n to 1-5 can take into account better heat resistance, strength, toughness and compactness. For example, the value of n is 1, 2, 3, 4 or 5.

[0048] The biomass polyester adhesive provided in the present application is a biodegradable polyester adhesive. Because its block unit has a furandicarboxylic acid structure, it has relatively high thermal stability, can maintain its structural integrity within a certain temperature range, and is not easy to decompose or denature. At the same time, because the block unit has a rigid structure of trimethylolmelamine resin, it has excellent heat resistance, good adhesion and adhesion. At the same time, the ether bond contained in it has flexibility and elasticity, which can alleviate the defect of insufficient toughness caused by the rigid structure of trimethylolmelamine resin, so that the biomass polyester adhesive has good stretchability, elasticity and durability. In addition, due to the polarity and low surface tension of the ether bond, the biomass polyester adhesive has good wetting performance.

[0049] In summary, the biomass polyester adhesive provided in the present application has better wetting performance, high heat resistance, good adhesion and durability. When the above-mentioned biomass polyester adhesive is applied to the coating of the diaphragm, it is beneficial to significantly reduce the contact angle of the coating and reduce the thermal shrinkage rate at 150°C for 1h, thereby improving the wetting performance and thermal stability strength of the coating surface, thereby enhancing the reliability and applicability of the diaphragm in practical applications.

[0050] In some optional embodiments, the value of n is 2 to 4. Within this range, the performance of the biomass polyester adhesive is further optimized.

[0051] Exemplarily, the value of n is 2, 3 or 4.

[0052] Preparation method of biomass polyester adhesive

[0053] The preparation method of the biomass polyester adhesive comprises:

[0054] Dissolving 2,5-furandicarboxylic acid ester and trihydroxymelamine resin alcohol in a first organic solvent to obtain a mixed solution, adding a first catalyst to the mixed solution and performing a polycondensation reaction under anaerobic conditions to obtain a biomass polyester adhesive;

[0055] The structural formula of 2,5-furandicarboxylic acid ester is as follows:

[0056] The value of n is 1-5;

[0057] The structural formula of trihydroxymelamine resin alcohol is as follows:

[0058]

[0059] The first catalyst includes a polyoxometalate.

[0060] The obtained biomass polyester adhesive has the following block units: wherein R1 and R2 are respectively segment repeating units or H, and at least one of the three R1s and the three R2s is a segment repeating unit,

[0061] Among them, the segment repeating unit is: The value of n is 1-5.

[0062] The anaerobic conditions involved in the present application can be obtained by repeatedly evacuating the reaction system and then introducing an inert gas, and the anaerobic conditions can avoid the generation of impurities.

[0063] n is related to the chain length of the alcohol ether structure in the 2,5-furandicarboxylic acid ester. The longer the chain length of the chain structure, the higher the viscosity of the polymer material, and the heat resistance, strength and toughness of the material will also be improved. Too long will reduce the compactness of the network structure. Therefore, the value of n is limited to 1-5, which can take into account better heat resistance, strength, toughness and compactness. Exemplarily, the value of n is 1, 2, 3, 4 or 5.

[0064] Optionally, the value of n is 2-4. The performance of the biomass polyester adhesive is further optimized within this range. Since the furandicarboxylic acid structure in 2,5-furandicarboxylic acid esters has a relatively high thermal stability, it can maintain its structural integrity within a certain temperature range and is not prone to decomposition or denaturation, which gives it certain advantages in heat treatment or high-temperature applications. Due to its unique rigid structure, trimethylolmelamine resin has excellent heat resistance and good adhesion and adhesion, but because of its high strength and rigidity, the toughness of the diaphragm is insufficient, affecting the safety of the battery. Ether alcohols have flexibility and elasticity due to their ether bonds, so that materials containing ether bonds have good tensile properties, elasticity and durability, and ether bonds usually exhibit good wetting properties due to their polarity and low surface tension.

[0065] Therefore, in the preparation method provided in the present application, the biodegradable polyester adhesive obtained by the condensation reaction using the above three as raw materials has better wetting performance, high heat resistance, good adhesion and durability. When the above biomass polyester adhesive is applied to the coating of the diaphragm, it is beneficial to significantly reduce the contact angle of the coating and reduce the thermal shrinkage rate at 150°C for 1h, thereby improving the wetting performance and thermal stability strength of the coating surface, thereby enhancing the reliability and applicability of the diaphragm in practical applications.

[0066] Among them, the first organic solvent can be an aprotic polar solvent, and the aprotic polar solvent includes but is not limited to one or more aprotic polar solvents such as N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), etc.

[0067] Optionally, the first organic solvent is dimethyl sulfoxide.

[0068] In some optional embodiments, the temperature of the polycondensation reaction is 130-150° C., and the time of the polycondensation reaction is 8-12 hours.

[0069] If the polycondensation reaction temperature is too low, the reaction rate will be too slow, resulting in a low molecular weight of the obtained polyester plastic, which will affect the performance. Therefore, by controlling the polycondensation reaction temperature and time within the above range, it is beneficial to obtain a suitable polycondensation reaction rate and to prepare a biomass polyester adhesive with a higher molecular weight.

[0070] Illustratively, the temperature of the polycondensation reaction is any one of 130°C, 132°C, 135°C, 137°C, 140°C, 143°C, 145°C, 147°C, 150°C, or between any two values.

[0071] Exemplarily, the polycondensation reaction time is any one of 8 h, 9 h, 10 h, 11 h, 12 h or between any two values.

[0072] In some optional embodiments, the molar ratio of trihydroxymelamine resin alcohol to 2,5-furandicarboxylic acid ester is 1:1.4-1.5.

[0073] Since the esterification reaction of the final biomass polyester adhesive is the condensation of one hydroxyl group of trihydroxy melamine resin alcohol (containing three hydroxyl groups) with one carboxyl group of a furandicarboxylic acid polyester (containing two carboxyl groups), the molar ratio of the two is controlled within the above range to make 2,5-furandicarboxylic acid ester slightly excessive. Slightly excessive 2,5-furandicarboxylic acid ester will not participate in the reaction, which is beneficial to ensure that the generated target product is the biomass polyester adhesive with high heat resistance and excellent wettability required by the present application.

[0074] Illustratively, the molar ratio of trihydroxymelamine resin alcohol to 2,5-furandicarboxylic acid ester is any one of 1:1.40, 1:1.42, 1:1.45, 1:1.47, 1:1.50, or between any two values.

[0075] In some optional embodiments, the molar ratio of 2,5-furandicarboxylic acid ester to the first catalyst is 4-5:1.

[0076] Illustratively, the molar ratio of the 2,5-furandicarboxylic acid ester to the first catalyst is any one of 4.0:1, 4.2:1, 4.5:1, 4.7:1, 5.0:1, or between any two values.

[0077] The method of adding the first catalyst to the mixed solution includes but is not limited to dropwise addition.

[0078] In some optional embodiments, the first catalyst is added to the mixed solution by constant flow dripping.

[0079] The constant flow dripping method is conducive to controlling the rate, making the reaction complete, and avoiding stratification. The specific dripping rate can be adjusted according to actual needs as long as stratification does not occur.

[0080] For example, the first catalyst can be added to the mixed liquid at a constant flow rate through a constant pressure funnel. The equipment is simple and easy to operate, which is conducive to reducing production costs.

[0081] In some optional embodiments, the 2,5-furandicarboxylic acid ester is prepared by the following method:

[0082] dissolving furandicarboxylic acid in a second organic solvent to obtain a furandicarboxylic acid solution;

[0083] Adding the ether alcohol and the second catalyst dropwise into the furandicarboxylic acid solution, stirring and performing an esterification reaction to obtain a 2,5-furandicarboxylic acid ester;

[0084] Among them, the structural formula of ether alcohol is as follows:

[0085] The value of n is 1-5;

[0086] The second catalyst includes a polyoxometalate.

[0087] n is related to the chain length of the alcohol ether structure. The longer the chain length of the chain structure, the viscosity of the polymer material will increase, and the heat resistance, strength and toughness of the material will also be improved. Too long will reduce the compactness of the network structure, so the value of n is limited to 1-5, which can take into account better heat resistance, strength, toughness and compactness. Exemplarily, the value of n is 1, 2, 3, 4 or 5. Optionally, the value of n is 2-4. The performance of the biomass polyester adhesive is further optimized within this range. Furan dicarboxylic acid (FDCA) has a very wide range of sources and is mainly produced by biomass resources. Therefore, furan dicarboxylic acid, a bio-based chemical with a wide range of sources, is used as a raw material to obtain 2,5-furan dicarboxylic acid esters, and then 2,5-furan dicarboxylic acid esters are used to synthesize excellent biomass polyester adhesives with melamine resin. Its green environmental protection, biodegradability and the characteristics of being used as a substitute for petroleum raw materials broaden the source of raw materials for synthesizing bio-based polyester adhesives, effectively reducing the production cost.

[0088] Among them, the second organic solvent can be an aprotic polar solvent, and the aprotic polar solvent includes but is not limited to one or more aprotic polar solvents such as N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), etc.

[0089] Optionally, the second organic solvent is dimethyl sulfoxide.

[0090] It should be noted that, in order to fully dissolve furandicarboxylic acid in the second organic solvent, furandicarboxylic acid and the second organic solvent may be mixed and then heated to 40-50° C. to fully dissolve the furandicarboxylic acid.

[0091] In some optional embodiments, the polyoxometallate includes silicotungstic acid and / or phosphotungstic acid.

[0092] In some optional embodiments, the molar ratio of furandicarboxylic acid to ether alcohol is 1:0.5-0.7.

[0093] Since the esterification reaction of furandicarboxylic acid polyester is a condensation of two hydroxyl groups of an ether alcohol (containing two hydroxyl groups) with a carboxyl group of furandicarboxylic acid (containing two carboxyl groups), the molar ratio of the two is controlled within the above range to make the furandicarboxylic acid slightly excessive. The slightly excessive furandicarboxylic acid will not participate in the reaction, which is conducive to ensuring that the target product 2,5-furandicarboxylic acid ester required by the present application is generated.

[0094] Illustratively, the molar ratio of furandicarboxylic acid to ether alcohol is any one of 1:0.50, 1:0.55, 1:0.60, 1:0.65, 1:0.70, or between any two values.

[0095] In some optional embodiments, the esterification reaction temperature is 70-90° C., and the esterification reaction time is 6-8 h.

[0096] Controlling the temperature and time of the esterification reaction within the above range is conducive to the full esterification reaction.

[0097] Illustratively, the esterification reaction temperature is any one of 70°C, 73°C, 75°C, 78°C, 80°C, 83°C, 85°C, 88°C, 90°C or between any two values.

[0098] Illustratively, the esterification reaction time is any one of 6.0 h, 6.5 h, 7.0 h, 7.5 h, 8.0 h, or between any two values.

[0099] In some optional embodiments, the molar ratio of furandicarboxylic acid to the second catalyst is 20-25:1.

[0100] By controlling the molar ratio of furandicarboxylic acid to the second catalyst within the above range, the esterification reaction rate can be controlled within an appropriate range.

[0101] Illustratively, the molar ratio of furandicarboxylic acid to the second catalyst is any one of 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, or between any two values.

[0102] In some optional embodiments, the ether alcohol and the second catalyst are first mixed and then added dropwise to the furandicarboxylic acid solution in a constant flow manner.

[0103] The method of mixing first and then dripping at a constant flow is conducive to controlling the rate, making the reaction complete, and avoiding stratification. The specific dripping rate can be adjusted according to actual needs as long as stratification does not occur.

[0104] For example, the ether alcohol and the second catalyst can be added to the mixed liquid at a constant flow rate through a constant pressure funnel. The equipment is simple and easy to operate, which is conducive to reducing production costs.

[0105] Diaphragm

[0106] The diaphragm includes a base film and a coating film located on the surface of the base film, and the coating film contains the biomass polyester adhesive provided by the present application.

[0107] The base film may be any known porous structure film with good chemical stability and mechanical stability. Exemplarily, the material of the base film includes but is not limited to at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The base film may be a single-layer film or a multi-layer composite film, without particular limitation. When the base film is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0108] The coating film is located on at least one surface of the base film. In addition to the biomass polyester adhesive provided in the present application, the coating film also contains other materials such as ceramic materials or high molecular polymers, which can be selected according to actual needs and are not limited here.

[0109] The diaphragm provided in the present application can effectively improve the high temperature resistance and wettability of the diaphragm and improve the electrochemical performance of the battery by adding the biomass polyester adhesive provided in the present application into the coating film.

[0110] In some optional embodiments, the mass percentage of the biomass polyester adhesive in the coating film is greater than 0 and less than or equal to 2%.

[0111] By controlling the mass percentage of the biomass polyester adhesive in the coating film within the above range, the diaphragm has better high temperature resistance and wettability.

[0112] In some optional embodiments, the mass percentage of the biomass polyester adhesive in the coating film is 1%-2%.

[0113] Controlling the mass percentage of the biomass polyester adhesive in the coating film within the above range is beneficial to further improve the high temperature resistance and wettability of the diaphragm.

[0114] Exemplarily, the mass percentage of the biomass polyester adhesive in the coating film is any value among 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.8%, 2%, or between any two values.

[0115] In some optional embodiments, the coating composition includes, by mass percentage: 67.50%-71.25% aluminum oxide, 3.75%-7.50% acrylamide polymer, 22.50% hexafluoropropylene, 2.50% acrylic acid, and greater than 0 and less than or equal to 2% of the biomass polyester adhesive.

[0116] Battery

[0117] A battery refers to a single physical module that includes one or more battery cells to provide a certain voltage and capacity. It can be in the form of a battery pack, battery module, etc. The battery may also include a box for encapsulating one or more battery cells. The box can prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells.

[0118] The battery cell refers to the smallest unit constituting the battery, and the battery cell includes the above-mentioned separator provided in the present application.

[0119] Electrical devices

[0120] The electrical device may be, but is not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.

[0121] The electrical device includes the battery provided in the present application, and the battery is used to supply power to the electrical device.

[0122] The biomass polyester adhesive and its preparation method, as well as the diaphragm, battery, and electrical device of the present application are further described in detail below in conjunction with the examples.

[0123] The biomass polyester adhesive and its preparation method, as well as the diaphragm, battery, and electrical device of the present application are further described in detail below in conjunction with the examples.

[0124] Contact angle test: the electrolyte was dropped onto the surface of the diaphragm sample, and the contact angle of the diaphragm and the electrolyte was tested using a video contact angle meter. The test was repeated 5 times and the average value was taken. The electrolyte was a 1 mol / L LiPF6 solution, and the solvent composition of the solution was a volume ratio of dimethyl carbonate DMC:ethylene carbonate EC:ethyl methyl carbonate EMC=1:1:1.

[0125] Thermal shrinkage test: Cut the coated diaphragm into a square with a side length of 10×10 cm, measure the length in the TD / MD direction as L1, clamp the diaphragm between two identical glass sheets, keep it in a constant temperature forced air drying oven at 150°C for 1h, and measure the length of the coating film in the TD / MD direction as L0; Thermal shrinkage rate = [(L1-L0) / L0]×100%.

[0126] Example 1

[0127]

Preparation of biomass polyester adhesive

[0128] Add 30.12g (0.2mol) of furan dicarboxylic acid and 25ml of dimethyl sulfoxide to a three-necked flask equipped with an electric stirrer, a temperature controller, a constant pressure dropping funnel, a reflux condenser and a nitrogen inlet tube, raise the temperature to 30-40°C, dissolve all the reactants, and vacuum the three-necked flask for about 1-2min, pass nitrogen for 1-3min, repeat 3 times, so that the reaction system is carried out in an oxygen-free environment. Use a 50ml disposable syringe to inject a mixture of 19.42g (0.1mol) of tetraethylene glycol and 0.12g of catalyst phosphomolybdic acid into the constant pressure dropping funnel, and inject all the raw materials and catalyst into the three-necked flask within 30 minutes. Heat to 70-90°C, and esterification reaction occurs for 6-8h under stirring and reflux. After the reaction is completed, the obtained reactant is washed with distilled water 3-4 times until the liquid is neutral, and the reaction liquid is decompressed and distilled, and vacuum dried at 60°C for 5h to obtain furan dicarboxylic acid polyester. Then, 35g (0.1mol) of furandicarboxylic acid polyester, 6.48g (0.03mol) of trimethylol melamine resin and 25ml of dimethyl sulfoxide were placed in a three-necked flask, and the three-necked flask was purged with nitrogen for 2 to 3 minutes, and then vacuumed for about 1 to 2 minutes, and repeated 3 times to remove the air in the reaction system. Use a 50ml disposable syringe to inject 0.18g of catalyst phosphomolybdic acid into the constant pressure dropping funnel, and inject all the catalyst into the three-necked flask within 30 minutes, heat it to 130-150°C, and esterify it under stirring and reflux for 8-12 hours. After the reaction is completed, the obtained reactant is washed with distilled water 3-4 times until the liquid is neutral, and the reaction solution is decompressed and distilled, and the final biomass polyester adhesive is obtained after vacuum drying at 60°C for 5 hours: biomass polyester adhesive.

[0129] The yield of the biomass polyester adhesive is calculated by the ratio of the final mass of the biomass polyester adhesive to the mass of the input raw material. In this embodiment, the yield of the biomass polyester adhesive is 68%, and Figure 1 This is the Fourier infrared spectrum of the biomass polyester adhesive prepared in Example 1 of the present application. Figure 1 Combined with the selection of raw materials, it can be concluded that the biomass polyester adhesive has the following block units:

[0130]

[0131]

Preparation of diaphragm

[0132] A biomass polyester adhesive is mixed with a slurry, wherein the addition amount of the biomass polyester adhesive is 1.5% of the mass of the slurry. The slurry includes 67.50% alumina, 7.50% acrylamide polymer, 22.50% hexafluoropropylene, and 2.50% acrylic acid by mass percentage to obtain a diaphragm slurry. The diaphragm slurry is applied to a base film (PE) and then dried. Finally, a contact angle of the coating is measured to be 16.8°. The coating has a thermal shrinkage of 0.93% in the MD direction and 1.02% in the TD direction at 150°C for 1 hour.

[0133] Example 2

[0134] The difference from Example 1 is that during the preparation of the diaphragm, the amount of biomass polyester adhesive added is 1% of the mass of the slurry. The diaphragm slurry is applied to the base film (PE) and then dried. The final contact angle of the coating is measured to be 22.8°. The coating shrinks by 1.32% in the MD direction and 1.25% in the TD direction at 150°C for 1 hour.

[0135] Example 3

[0136] The difference from Example 1 is that: during the preparation of the diaphragm, the amount of biomass polyester adhesive added is 2% of the mass of the slurry. The diaphragm slurry is applied to the base film (PE) and then dried. The final contact angle of the coating is measured to be 19.4°; the coating shrinks by 1.02% in the MD direction and 1.06% in the TD direction at 150°C for 1 hour.

[0137] Example 4

[0138] The difference from Example 1 is that during the preparation of the biomass polyester adhesive, 0.1 mol of tetraethylene glycol (19.42 g) was replaced by 0.1 mol of triethylene glycol (15 g). The measurement result was: the yield was 69%.

[0139] During the preparation of the diaphragm, the amount of biomass polyester adhesive added was 1.5% of the slurry mass. The diaphragm slurry was applied to the base film (PE) and dried. The final contact angle of the coating was measured to be 21.4°. The thermal shrinkage of the coating at 150°C for 1 hour was 1.16% in the MD direction and 1.22% in the TD direction.

[0140] Example 5

[0141] The difference from Example 4 is that: during the preparation of the diaphragm, the amount of biomass polyester adhesive added is 2% of the mass of the slurry. The diaphragm slurry is applied to the base film (PE) and then dried. The final contact angle of the coating is measured to be 21.1°; the coating shrinks by 1.29% in the MD direction and 1.32% in the TD direction at 150°C for 1 hour.

[0142] Example 6

[0143] The difference from Example 1 is that during the preparation of the biomass polyester adhesive, 0.1 mol of tetraethylene glycol (19.42 g) was replaced by 0.1 mol of diethylene glycol (10.06 g). The measurement result was: the yield was 66%.

[0144] During the preparation of the diaphragm, the amount of biomass polyester adhesive added was 1.5% of the slurry mass. The diaphragm slurry was applied to the base film (PE) and dried. The final contact angle of the coating was measured to be 24.6°. The coating shrank by 1.31% in the MD direction and 1.42% in the TD direction at 150°C for 1 hour.

[0145] Example 7

[0146] The difference from Example 6 is that: during the preparation of the diaphragm, the amount of biomass polyester adhesive added is 2% of the mass of the slurry. The diaphragm slurry is applied to the base film (PE) and then dried. The final contact angle of the coating is measured to be 24.3°. The coating shrinks by 1.28% in the MD direction and 1.43% in the TD direction at 150°C for 1 hour.

[0147] Example 8

[0148] The difference from Example 1 is that during the preparation of the biomass polyester adhesive, 0.2 mol of furan dicarboxylic acid (30.12 g) was added instead of 0.22 mol of furan dicarboxylic acid (34.32 g). The measurement result was: the yield was 72%.

[0149] During the preparation of the diaphragm, the amount of biomass polyester adhesive added was 1.5% of the slurry mass. The diaphragm slurry was applied to the base film (PE) and dried. The final contact angle of the coating was measured to be 17.2°. The coating shrank by 1.02% in the MD direction and 1.0% in the TD direction at 150°C for 1 hour.

[0150] Example 9

[0151] The difference from Example 1 is that during the preparation of the biomass polyester adhesive, 0.03 mol of trimethylol melamine resin (6.48 g) was replaced by 0.05 mol of trimethylol melamine resin (10.8 g). The measurement result was: the yield was 52%.

[0152] During the preparation of the diaphragm, the amount of biomass polyester adhesive added was 1.5% of the slurry mass. The diaphragm slurry was applied to the base film (PE) and dried. The final contact angle of the coating was measured to be 27.3°. The coating shrank by 0.82% in the MD direction and 0.93% in the TD direction at 150°C for 1 hour.

[0153] Comparative Example 1

[0154] The difference from Example 1 is that: no biomass polyester adhesive is added during the preparation of the biomass polyester adhesive, the slurry is directly applied to the base film and then dried, and the final measured contact angle of the coating is 36.8°; the coating shrinks 3.13% in the MD direction and 2.53% in the TD direction at 150°C for 1 hour.

[0155] From the comparison between the above examples and the comparative examples, it can be seen that the present application can synthesize a biomass polyester adhesive with excellent performance. After using it in the separator, the contact angle of the coating can be improved to below 25°, and the thermal shrinkage rate of the coating at 150°C for 1h is below 2%. Through the application of this new adhesive, the wetting performance of the coating surface will be significantly improved, and the thermal stability strength of the coating is relatively high, which can effectively enhance its reliability and applicability in practical applications.

[0156] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A biomass polyester adhesive, characterized in that: It has block units as shown below: wherein R1 and R2 are respectively a segment repeating unit or H, and at least one of the three R1s and the three R2s is the segment repeating unit, Wherein, the segment repeating unit is: The value of n is 1-5.

2. A method for preparing a biomass polyester adhesive, characterized in that: include: Dissolving 2,5-furandicarboxylic acid ester and trihydroxymelamine resin alcohol in a first organic solvent to obtain a mixed solution, adding a first catalyst to the mixed solution and performing a polycondensation reaction under anaerobic conditions to obtain the biomass polyester adhesive; Wherein, the structural formula of the 2,5-furandicarboxylic acid ester is as follows: The value of n is 1-5; The structural formula of the trihydroxy melamine resin alcohol is as follows: The first catalyst includes a polyoxometalate.

3. The preparation method according to claim 2, characterized in that: The temperature of the polycondensation reaction is 130-150° C., and the time of the polycondensation reaction is 8-12 hours.

4. The preparation method according to claim 2, characterized in that: The molar ratio of the trihydroxymelamine resin alcohol to the 2,5-furandicarboxylic acid ester is 1:1.4-1.

5.

5. The preparation method according to claim 2, characterized in that: The molar ratio of the 2,5-furandicarboxylic acid ester to the first catalyst is 4-5:

1.

6. The preparation method according to claim 2, characterized in that: The first catalyst is added into the mixed solution by constant flow dripping.

7. The preparation method according to any one of claims 2 to 6, characterized in that: The 2,5-furandicarboxylic acid ester is prepared by the following method: dissolving furandicarboxylic acid in a second organic solvent to obtain a furandicarboxylic acid solution; Adding the ether alcohol and the second catalyst dropwise into the furandicarboxylic acid solution, and performing an esterification reaction under anaerobic conditions to obtain the 2,5-furandicarboxylic acid ester; Wherein, the structural formula of the ether alcohol is as follows: The value of n is 1-5; The second catalyst comprises a polyoxometalate; Optionally, the value of n is 2-4.

8. The preparation method according to claim 7, characterized in that: The molar ratio of the furandicarboxylic acid to the ether alcohol is 1:0.5-0.

7.

9. The preparation method according to claim 7, characterized in that: The temperature of the esterification reaction is 70-90° C., and the time of the esterification reaction is 6-8 hours.

10. The preparation method according to claim 7, characterized in that: The molar ratio of the furandicarboxylic acid to the second catalyst is 20-25:

1.

11. The preparation method according to claim 7, characterized in that: The ether alcohol and the second catalyst are first mixed, and then added into the furandicarboxylic acid solution by constant flow dropwise addition.

12. The preparation method according to any one of claims 2 to 6, characterized in that: The polyoxometallate includes silicotungstic acid and / or phosphotungstic acid.

13. A diaphragm, characterized in that: It comprises a base film and a coating film located on at least one surface of the base film, wherein the coating film contains the biomass polyester adhesive according to claim 1 or the biomass polyester adhesive prepared by the preparation method according to any one of claims 2-12.

14. The diaphragm according to claim 13, characterized in that The mass percentage of the biomass polyester adhesive in the coating film is greater than 0 and less than or equal to 2%; Optionally, the mass percentage of the biomass polyester adhesive in the coating film is 1%-2%.

15. A battery, characterized in that: The diaphragm according to claim 13 or 14.

16. An electrical device, characterized in that: The battery according to claim 15 is used to supply power to the electrical device.